Journal Sharing on Group Cohesion and Goal Attainment in Experiential Growth Groups. Issue 3 (3rd July 2018) - Oh, Seungbin; Mitchell, Michelle D.; McKinzie Bennett, Caitlyn; Rendon Finnell, Laura; Saliba, Yvette; Heard, Nevin J.; Pennock, Elizabeth R.
Abstract : This study investigated the effect of journal sharing in counselor education experiential growth groups. Outcome measures included change in group cohesion over time and rate of group cohesion change after controlling for level of goal attainment. Counseling students were assigned to either treatment (i.e., journal sharing; n = 38) or control groups (i.e., non-journal sharing; n = 24). The control groups that did not share journals showed a significantly faster growth of the group cohesion than journal sharing groups. Implications for future research and counselor education programs are presented.